Diagram editing with hypergraph parser support - Minas, Mark (Proceedings of the 1997 IEEE Symposium on Visual Languages (VL '97), 1997)
Diagrams are always used when communicating complex situations. Diagram editors support the user when editing diagrams on a computer. However, creating diagram editors is expensive and time-consuming. Frameworks that can be customized for the specific diagram classes considerably reduce these costs. In previous work, the framework DiaGen using an internal hypergraph model and offering syntax-directed editing had been introduced. This paper presents an incremental hypergraph parser and an extension of DiaGen that allows for editing diagrams like in a drawing tool. The hypergraph parser detects correct (sub-) diagrams online and notifies the user of incorrect diagram parts. This allows editing with temporally inconsistent diagrams which supports a natural editing style.
UnivIS-Import:2015-04-16:Pub.1997.tech.IMMD.IMMD2.diagra